ChemInform Abstract: Silylation‐Based Kinetic Resolution of α‐Hydroxy Lactones and Lactams. Issue 21 (27th May 2014) - Clark, Robert W.; Deaton, T. Maxwell; Zhang, Yan; Moore, Maggie I.; Wiskur, Sheryl L.
Abstract Triphenylsilyl chloride in combination with catalytic amounts of (‐)‐benzotetramisole (BAM) allows the non enzymatic kinetic resolution of α‐hydroxy esters and amides.